2016
DOI: 10.1051/0004-6361/201526845
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field geometry of an unusual cometary cloud Gal 110-13

Abstract: Aims. We carried out optical polarimetry of an isolated cloud, Gal 110-13, to map the plane-of-the-sky magnetic field geometry. The main aim of the study is to understand the most plausible mechanism responsible for the unusual cometary shape of the cloud in the context of its magnetic field geometry. Methods. When unpolarized starlight passes through the intervening interstellar dust grains that are aligned with their short axes parallel to the local magnetic field, it gets linearly polarized. The plane-of-th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…But, in principle, to obtain the actual magnetic field morphology in a cloud, the foreground polarization contribution has to be excluded. From the previous polarization studies by us towards the clouds located at distances less than ∼500 pc (e.g., Soam et al, 2013;Neha et al, 2016) and from the literature (Li et al, 2009), it was found that the change occurred to the values of the θP after correcting for the foreground contribution is not noteworthy specially if the observed P is relatively higher (i.e. 1%).…”
Section: Subtraction Of Interstellar Polarizationmentioning
confidence: 82%
See 1 more Smart Citation
“…But, in principle, to obtain the actual magnetic field morphology in a cloud, the foreground polarization contribution has to be excluded. From the previous polarization studies by us towards the clouds located at distances less than ∼500 pc (e.g., Soam et al, 2013;Neha et al, 2016) and from the literature (Li et al, 2009), it was found that the change occurred to the values of the θP after correcting for the foreground contribution is not noteworthy specially if the observed P is relatively higher (i.e. 1%).…”
Section: Subtraction Of Interstellar Polarizationmentioning
confidence: 82%
“…The instrumental polarization of AIMPOL has been 4.5 ± 0.1 116 ± 1 † Values in R band from Schmidt et al (1992) ‡ Values in V band from Schmidt et al (1992) checked by observing un-polarized standards and found nearly invariable with a value of ∼ 0.1% by Soam et al (2013Soam et al ( , 2015 and Neha et al (2016). The polarized standard stars observed by us to calibrate our polarization values are summarized in Table 2.…”
Section: Optical Polarizationmentioning
confidence: 99%
“…The instrumental polarization of AIMPOL is generally found to be small, at ∼ 0.1 per cent (see, e.g. Medhi et al 2007;Pandey et al 2009;Das et al 2013;Eswaraiah et al 2012Eswaraiah et al , 2013Patel et al 2013;Soam et al 2015;Neha et al 2016;Rakshit et al 2017;Wang et al 2017;Lee et al 2018, and references therein). This was verified by the observations of the unpolarized standard star HD 12021 (Schmidt, Elston & Lupie 1992).…”
Section: Standard Starmentioning
confidence: 99%
“…Thus, the stars, which are classified as main sequence stars, are plotted in an A V versus distance diagram to estimate the distance of the cloud. This method was used to estimate distances to a number of clouds (e.g., Maheswar et al, 2011;Soam et al, 2013;Eswaraiah et al, 2013;Neha et al, 2016). In Fig.…”
Section: From the 2mass Photometrymentioning
confidence: 99%